Molecular Biology of Breast Cancer in the Horn of Africa: Case Series—A Pilot Study of Breast Cancer from Eritrea. (3rd June 2013) - Tesfamariam, Asmerom; Roy, Indrojit
Abstract : Background . Recently, gene expression profiling and its surrogate immunohistochemistry (IHC) markers classified breast cancer into four distinct molecular subtypes, which have different prognoses, targeted therapies, and/or clinical outcomes. Objective . To conduct a preliminary study, to correlate the clinical pathological profiles and taxonomy of molecular subtypes of breast cancer in Eritrea, in the Horn of Africa. Design . Review of pathology reports from Jan. 1 to Nov. 30, 2009, provided 22 cases of microscopically confirmed invasive breast carcinoma that were evaluable for histology and IHC (ER, PR, HER2, and Cytokeratin 5/6). Result . Twenty patients were female and most of them (68%) were under 50 years at presentation. 90% were invasive invasive carcinoma of no special type and were histological grade 3. The molecular subtypes were luminal A (55%), luminal B (5%), HER2 (5%), basal-like (10%), and unclassified (25%). Triple negative carcinoma (basal-like and unclassified combined) was 35%, mostly (71%) in women under 50 years with grade 3 tumours. Conclusion . Breast carcinoma in Eritrean women presents at a younger age and with a high histologic grade. The two predominant molecular subtypes are luminal A and triple negative. Determining the molecular subtype using surrogate IHC markers has important treatment and prognostic implications for Eritrean women with breast cancer.